Mixing characteristics of 45° inclined duckbill dense jets in co-flowing currents - Jiang, Mingtao (2022)
The use of duckbill valves in submerged outfalls for dense effluents is now prevalent to prevent the intrusion of ambient water into the outfall pipe during periods of low production of the facility. In the present study, an experimental investigation was conducted using the technique of Planar Laser Induced Fluorescence (PLIF) to examine the mixing characteristics of 45° inclined dense jets from a duckbill shape nozzle in co-flowing currents. The measured characteristics included the jet trajectory, concentration decay, centreline peak dilution and cross-sectional concentration distribution. The Froude number ranged from 10 to 25, and the nominal Froude number from 0.2 to 3.0. Two mounting orientations of the duckbill nozzle, namely vertical and horizontal, were also investigated. The experimental results showed that two regimes, namely dense-jet- and co-flow-dominated, can be clearly observed. When the co-flow velocity increases, the centreline peak height and dilution of the inclined dense jet decrease. Comparing to the available results in the literature for inclined circular dense jets, the centreline peak dilution for inclined duckbill dense jets is generally higher. In other words, the installation of the duckbill valve also contributes to the mixing of the dense effluent with surrounding ambient waters, in addition to preventing the ambient intrusion. With respect to the mounting orientation, the horizontal induces a relatively higher dilution but also a larger centreline peak height. Thus, the horizontal orientation would be preferable when the cover water depth is sufficient, while the vertical orientation can be considered in shallow waters for full submergence.